Diiron butane-1, 2-dithiolate complexes with tris(2-thienyl)phosphine, tris(4-trifluoromethylphenyl)phosphine, or 4-(dimethylamino)phenyldiphenylphosphine: synthesis, characterization, X-ray crystal structures, and electrochemistry. (2nd May 2020) - Lin, Hui-Min; Wang, Ling-Hui; Li, Ao; Xiao, Qi-Min; Liu, Xu-Feng; Li, Yu-Long; Liu, Xing-Hai; Jiang, Zhong-Qing
Abstract: In this paper, three diiron butane-1, 2-dithiolate complexes have been prepared and characterized. Treatment of the starting complex [Fe2 (CO)6 { µ -SCH2 CH(CH2 CH3 )S}] (1 ) with a monophosphine ligand tris(2-thienyl)phosphine, tris(4-trifluoromethylphenyl)phosphine, or 4-(dimethylamino)phenyldiphenylphosphine and Me3 NO·2H2 O as the decarbonylating agent gave the target products 2 ‒4 in 75‒91% yields. These complexes have been characterized by elemental analysis, IR, NMR spectroscopy, as well as by X-ray crystallography. Moreover, the electrochemical properties of complexes 3 and 4 were investigated by cyclic voltammetry.